Caption Contest (The Biblical archaeology review, 2026)
Thank you to all those who submitted caption entries for our Fall 2025 cartoon (left), based on Genesis 11:6-7: "And the LORD said, ‘Look, they are one people, and they have all one language, and this is only the beginning of what they will do; nothing that they propose to do will now be impossible […]